Evaluation of fluctuating asymmetry and sexual dimorphism of Channa striata using landmark-based geometric morphometric analysis from Agusan Marsh and Lake Mainit in Caraga Region, Philippines - Rex Bomvet Saura; Geneveve Falcasantos; Rex Jr. Andante; Luna Munda; Marycris Alimorong; Brent Joy Hernando (Smujo International, 2021)
Abstract. Saura EBD, Falcasantos GC, Andante RJM, Munda LC, Alimorong MM, Hernando BJ. 2021. Evaluation of fluctuating asymmetry and sexual dimorphism of Channa striata using landmark-based geometric morphometric analysis from Agusan Marsh and Lake Mainit in Caraga Region, Philippines. Nusantara Bioscience 13: 100-110. Evaluation was conducted to determine the impact of ecological condition to Channa striata using fluctuating asymmetry (FA) employing the landmark-based geometric morphometric analysis, using TPS software, SAGE, PAST-Hotellings Test, including Physico-chemical analysis, cyanide and four base metals. Results of Physico-chemical analysis of the two habitats showed Agusan marsh with low oxygen level (3.37-4.55) and high in Iron and TDS as compared to DENR Standards. The statistical results showed high variations (p < 0.0001) on left and right-side having percentage of 79.22% in Agusan Marsh and 72.35% in Lake Mainit which is relatively high Fluctuating Asymmetry. In terms of sex, Agusan marsh had 84.27% and 85.41% FA in males and females while Lake Mainit having 85.12% and 80.89% in males and females. The fairly similar percentage of Fluctuating Asymmetry confirms no sexual dimorphism and no shape differences between male and female, and no peculiar characters to distinguished between sexes based on the 17 landmark points. Present study concluded that FA observed in the snout tip was due to breeding behavior, the landmark points in cephalic, pectoral, and caudal region were associated with burrowing and mobility factors within the lateral line system in these fishes which thrive in high turbid habitat and low oxygen. Furthermore, it was found that the level of FA tends to increase in disturbed environs.